IDENTIFIKASI KUALITAS DAN BOBOT MASA SIMPAN BEBERAPA JENIS BUAH SALAK BALI (Salacca Zalacca Var. Amboinensis) - Ni Kadek Emawati; I Dewa Nyoman Raka; I Made Suryana; Farida Hanum; Putu Eka Pasmidi Ariati (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
Bali salak fruit is one of the preferred fruit plants and has good prospects for cultivation. and the production of salak fruit is very large. This study, entitled